Handbook of optical and laser scanning - Marshall, Gerald F.; Stutz, Glenn E. ([S.l.] : CRC Press, 2004)
The Handbook of Optical and Laser Scanning reveals the fundamentals of controlling light beam deflection, factors in image fidelity and quality, and the newest technological developments currently impacting scanner system design and applications. This highly practical reference features a logical chapter organization, authoritative yet accessible writing, and hundreds of supporting illustrations. Contributions from 27 subject specialists from the United States, Europe, and Asia afford a valuable range of perspectives as well as global coverage of optical and laser beam scanning. With more than 550 works cited, this Handbook is essential for optical engineers, technologists, scientists, and undergraduate and graduate students in these disciplines. About the Editor: GERALD F. MARSHALL is a Consultant in Optical Design and Engineering, Niles, Michigan. Specializing in optical scanning and display systems, his extensive experience includes senior positions with Kaiser Electronics, San Jose, California; Energy Conversion Devices, Troy, Michigan; Axsys Technologies (formerly Speedring Systems), Rochester Hills, Michigan; and Medical Lasers, Burlington, Massachusetts. Previously he was engaged as a Senior R&D Engineer for airborne navigational display systems at Ferranti Ltd., Edinburgh, Scotland, and as a Physicist with Morganite International Ltd., London, England. The author of many papers, he holds a number of patents and is the editor of two internationally recognized reference books, Laser Beam Scanning and Optical Scanning (both titles, Marcel Dekker, Inc.). He is a Fellow of The Institute of Physics, the Optical Society of America, and SPIE-The International Society for Optical Engineering, of which he is a former director. He received the B.Sc. degree from London University, England.